Quality of Life and Compliance Based On Hypertension Patient Characteristics At Krobokan Primary Health Center West Semarang District - Gilang Rizki Al Farizi; Rissa Maharani Dewi; Fransica Gloria; Hartika Widiya (Universitas Wahid Hasyim Semarang, 2024)
Hypertension is the chronic diseases that is a health problem in Indonesia. According to the Basic Health Research 2018 the hypertension population in Indonesia is around 34.1% at the age of ≥18 years. Every year hypertension sufferers are increasing, around 29% of adults suffer from hypertension worldwide. Patients with hypertension require long therapy even for life which certainly makes patients continuously consume antihypertensive drugs which can ultimately affect patient compliance and quality of life. The purpose of the study was to determine description of quality of life and adherence based on hypertention patient at Krobokan Primary Health Center, West Semarang district. This study used a quantitative design with observational research and a cross-sectional approach conducted in the period March-May 2023. The instruments used were MMAS-8 and HRQOL SF-36 as many as 53 samples who met the inclusion criteria. The results showed that the highest respondent characteristics were female 36 (68%), age 56 - 65 years 26 (49%), high school 18 (34%), housewives 31 (58%), length of hypertension ≥ 2 years 27 (51%), one of hypertention drug taken 50 (94%), suffering from other illnesses 23 (43%) and moderate adherance 36 (68%). In the domains of energy, emotional role, physical role, physical function and general health had a low quality of life in most patients with moderate adherence